"رواج نامہ سوات " میں موجودٹریفک کے متعلق والئی سوات کے حکم ناموں کا شرعی و تحقیقی جائزہ (Al-Qamar, 2024)
Being benefited by the favors of Allah Ta'ala, man is eager to find more facilities for himself every time and is busy day and night to make every area of ​​life easier. But it is also surprising that on the one side, man wants facilities for himself, while on the other side, sometimes these facilities are the cause of death. As in earlier times people used to travel on Donkey Carts, Camels etc. Then times changed and engines started being used, people started traveling in cars. Development progressed until the time of the airplane came. People traveled the journey of month in hours. But along with this accidents also started to increase. Accidents in the past caused very few deaths, while today's accidents cause many deaths or at least maiming and injuring the human body or causing financial loss. After which the parties file various claims against each other. Therefore, keeping in mind the Islamic principle, it is necessary to resort to Sharia law to solve these problems. Because nowadays traffic usage is very high due to the abundance of people and it is increasing day by day. Due to which traffic problems are also faced more. Therefore, all countries and states issue orders for the traffic problems like all others problems of the country. For this reason, the Wali Swat also issued some orders for the residents of his successful state. Six of these orders are mentioned in the Riwaj Nama Swat, which are being reviewed in the light of Sharia in this article.
Keywords: Airplane; Donkey Carts; Riwaj Nama e Swat; Wali Swat Decrees Regarding Traffic